Sustainability in biofuel production technology - Agrawal, Pratibha (Professor); Belkhode, Pramod; Rokhum, Samuel Lalthazuala (Wiley, 2023)
"This book highlights the source of renewable energy biofuels which will save natural resources and minimize the impact of fossil fuels. This book provides detailed information about the challenges and recent trends in biodiesel production which will be useful for future researchers and industrialists in biodiesel production at global level. Authors extend the scope of this book to process equipment such as types of reactors, reactor design, safety considerations, performance analysis with cost estimation. Topics include: Biofuels for aviation- Chemistry of fuel molecules, Alcohol to Jet, Oil to jet, Gas to Jet, Sugar to Jet fuel, Overview of blending sustainable aviation fuel Biofuel production technologies- Development of chemical conversion technologies, Development of thermos-chemical conversion technologies, Development of biological conversion technologies, Development of bio-chemical conversion technologies, Process integration and biorefinery Reactor designing and safety considerations- Limitation of conventional production technology, Ideal reactors, Reactor designing from engineering aspect, Process parameters in reactor designing, Reactor designing, Safety considerations in reactor designing, Capital cost and performance analysis of reactor Modelling and simulation for Biofuel production- Parameters affecting biofuel production, Mathematical model formulation, Artificial Neural Network Simulation, Uncertainty analysis, Sensitivity analysis, Optimization of Model, Reliability of the Model Analysis of Performance of the Model."- Resumé vydavatel
Keywords: fytoenergetika; inovace; alternativní energetické zdroje; biopaliva; biomass energy; innovations; alternative energy sources; biofuels; elektronické knihy; monografie; electronic books; monographs